Status of soil cover on the degree of accumulation of heavy metals in the soil of the industrial region (Karaganda city) - Мukasheva, М.А.; Мukasheva, G.Zh.; Surzhikov, D.V.; Arymbekova, А.K.; Zernke, B. (KSU publ., 2017)
In article the condition of a soil cover of the city of Karaganda is studied. Well adjusted system of monitoring by estimates of accumulation of metals in objects of a surrounding medium is necessary for carrying out the bioremediation of actions. The developed system will allow to determine consistent patterns of formation of technogenic load of the soil with a sufficient degree of accuracy. In the analysis of accumulation in the soil, it is necessary to take into account the frequency and the dynamics of the research, the number of points of comparison. In addition, to assess bioremediation measures must take into account views of the environment, the amount, location and frequency of sampling, certain requirements for the methodological and technical support.
Өндіріс аймағының топырағында ауыр металдардың жинақталу дəрежесіне байланысты топырақ қабатының жағдайы (Қарағанды қаласы)
Состояние почвенного покрова по степени накопления тяжелых металлов в почве промышленного региона (город Караганда)
Keywords: residential area; the soil; lead; method of stripping voltammetry; industrial district; environment; chemical pollution